Finance and Development, September 1983. (Finance and Development; Finance and Development, 1983)
This paper presents a review of the principal issues emerging from an IMF Conference held in March 1983. The special drawing right has been conceived in the 1960s and has been formally provided in the first amendment to the Articles of Agreement of the IMF, which took effect in 1969. Upon the abandonment of the Bretton Woods system of fixed exchange rates and the coming of freedom for the IMF members to adopt the exchange arrangements of their choice, a lack of discipline has been felt in the international monetary system.